What’s in the Song? Urtyn duu as Sonic “Ritual” Among Mongolian Herder-singers - Yoon, Sunmin (MUSICultures, 2019)
While contemporary Mongolia experiences a rapid expansion of its global urbanized culture, its rural nomadic culture remains central to its inhabitants’ traditional worldview, albeit described using nationalistic and nostalgic imagery. Drawing on the essential ideas of Naess’s Deep Ecology, and looking particularly at the folksong genre of urtyn duu, this article examines regular events in the countryside, characterized by human interaction with livestock and with the landscape, and their relevance to the performative, textual, and sonic elements of urtyn duu. It suggests that the act of singing among herder-singers transcends the separateness of the actors within the ecosystem, and so ritualizes the practice of urtyn duu as a way to balance the environment. Considering recent ecomusicological approaches, this paper seeks to understand urtyn duu within the ontological ecosystem through the lens of spirituality.